College students in the United States : characteristics, experiences, and outcomes - Renn, Kristen A. (Jossey-Bass higher and adult education series., 2013)
"College Students in the United States accounts for contemporary and anticipated student demographics and enrollment patterns, a wide variety of campus environments and a range of outcomes including learning, development, and achievement. Throughout the book, the differing experiences, needs, and outcome of students across the range of "traditional" (18-24 years old, full-time students) and non-traditional (for example, adult and returning learners, veterans, recent immigrants) are highlighted. The book is organized, for use as a stand-alone resource, around Alexander Astin's Inputs-Environment-Outputs (I-E-O) framework"--